Zimbabwean women online: an investigation of how gendered identities are negotiated in Zimbabwean women's online spaces - Ndlovu, Nonhlanhla (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
This study is concerned with the construction of Zimbabwean women's identities in this contemporary internet age. Two Facebook groups are of particular interest here due to the vibrant conversations that take place on a daily basis, that is, Makhox Women's League and Baking & Cooking: ZW Women's Diaries. Conceiving these internet sites as discursive spaces, I unpack the contesting discourses and tensions in the different narratives offered by Zimbabwean women and identify and critique the competing sets of feminine subjectivities. I achieve this by drawing on poststructuralist and postcolonialist feminist theories in order to situate these groups as cultural sites that are particularly identity defining. I particularly draw on Foucauldian theories of discourse, power and the subject to conceptualise the formation of particular discursive gendered subjectivities. With an understanding that discourse is constitutive of power relations and contestations, and that discourse should be historically contextualised in order to take into account particular conditions of existence; I draw on Mamdani's (1996) conceptualisation of how power is organised in Africa within a historical and institutional context, and identify the bifurcated nature of the postcolonial Zimbabwean state as a colonial residue as necessitating a particular kind of subjectivity. To this end, one can understand the different femininities on Makhox Women's League and Baking & Cooking: ZW Women's Diaries as constituted within, and complexly negotiating, a traditional/customary discourse and a rights-based modern one. This qualitative inquiry is informed by an eclectic approach that combines methods of textual analysis that complements both critical linguistics and media studies and attends to lexical structure as well as narrative and rhetorical analysis respectively. Combined with an online ethnographic approach I employ these tools to analyse these particular Facebook groups with the understanding that as women converse daily on these platforms, they 'govern' each other's conduct and thought processes in interesting ways. I argue that these conversations discursively constitute the performances of different femininities on both sites that also take into account the diasporic condition of Zimbabwean women. I show how they negotiate and mediate feminine performance and in so doing propose and contest certain 'truths' that are frequently validated.
Keywords: Woman -- Zimbabwe -- Social life and customs; Social media -- Social aspects -- Zimbabwe; Facebook (Firm); Women -- Zimbabwe